Diagnostic value of Candida mannan antigen and anti‐mannan IgG and IgM antibodies for Candida infection. Issue 2 (15th December 2019) - Wang, Kaifei; Luo, Yanping; Zhang, Wei; Xie, Sheling; Yan, Peng; Liu, Yang; Li, Yanqin; Ma, Xiuqing; Xiao, Kun; Fu, Han; Cai, Jinyu; Xie, Lixin
Summary: Objective: To assess the diagnostic value of serum Candida mannan antigen (MN) and anti‐mannan IgG and IgM antibodies for candidiasis. Methods: This study was a prospective cohort study. Clinical data and venous blood samples from 23 medical centres in Beijing, China were collected between 1 January 2017 and 31 December 2018. All collected specimens were tested within one week for serum Candida MN and IgG and IgM antibodies using an ELISA kit. Results: A total of 452 patients were enrolled, including 188 patients in the Candida exposure groups (56 patients with Candida bloodstream infection, 69 patients with Candida ‐positive tracheal aspirate cultures and 63 patients with Candida ‐positive urine cultures) and 264 patients in the control groups (212 healthy controls and 52 patients with bacteraemia). The receiver operating characteristic (ROC) curve of the 56 patients with Candida bloodstream infection and 212 healthy controls showed that serum MN and IgG had good diagnostic value. The area under the ROC curve (AUC) values were 0.812 (95% CI, 0.750‐0.873) and 0.866 (95% CI, 0.808‐0.924), respectively, wherein the MN specificity and sensitivity were 86.79% and 60.71%, and the IgG were 84.43% and 80.36%, respectively. The AUC of the combination of serum MN and IgG was 0.871(95% CI, 0.813‐0.929), and the specificity and sensitivity were 93.87% and 57.14%. Conclusions: The serum levels of Candida MN and its IgG antibody have diagnostic value for Candida bloodstream infection, and combination of MN and IgG can improve diagnostic specificity and may provide a new approach for diagnosis of candidaemia.